2020
DOI: 10.1016/j.apmt.2020.100782
|View full text |Cite
|
Sign up to set email alerts
|

Large volume nanoscale 3D printing: Nano-3DP

Abstract: 3D printers suffer from the inverse relationship between throughput and minimum feature size; with smaller features inducing a cubic increase in print time. Here we introduce Nano-3DP, a hybrid process that combines digital light projection 3D printing with nanoscalerelief patterning. The tool enables large volume (cm 3 ) prints with nanoscale details at a truly rapid rate (~120 mm/hour). 40 nm features, half the size of the finest printed details to date, are produced across a scalable print volume. We addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Gadegaard et al [ 156 ] have demonstrated an interesting approach of 3D printing over a large volume with high resolution features by combining nanoimprinting with DLP—where the nanopatterns are created using electron beam lithography and reactive ion etching—and with the part being used as insert for injection moulding. Such an approach could allow higher volume manufacture of microfluidic devices which combine microfluidic channels with other elements such as gratings and fluidic filters.…”
Section: Low-volume Productionmentioning
confidence: 99%
“…Gadegaard et al [ 156 ] have demonstrated an interesting approach of 3D printing over a large volume with high resolution features by combining nanoimprinting with DLP—where the nanopatterns are created using electron beam lithography and reactive ion etching—and with the part being used as insert for injection moulding. Such an approach could allow higher volume manufacture of microfluidic devices which combine microfluidic channels with other elements such as gratings and fluidic filters.…”
Section: Low-volume Productionmentioning
confidence: 99%
“…Not surprisingly, variations of SLA printings have also been reported, such as two-photon polymerization (2PP). 2PP relies on a modification of the laser optics and is capable of improving feature resolution down to the nanometer length scale [70]. Of all the 3D printing techniques currently available, 2PP has superior resolution and is capable of fabricating high-quality optical surfaces and microstructures with considerable complexity.…”
Section: D Printingmentioning
confidence: 99%
“…[38] One of the principal advantages of 3D printing is that it enables planar and 3D architectures to be patterned with controlled composition and structure across a range of length scales spanning from hundreds of nanometers to 1 m or larger. [39] Ink chemistries are tailored to simultaneously satisfy requirements for printability as well as the desired materials properties in the final fabricated structure. [29,[40][41][42] Stereolithography, Digital Light Processing, and DIW serve as important exemplars of 3D printing methods, each harboring specific advantages as a means of 3D fabrication and having different requirements to achieve high print speed and resolution.…”
Section: D/4d Printing Of Soft Mattermentioning
confidence: 99%